ANALISIS FAKTOR SOSIODEMOGRAFI KELAHIRAN PREMATUR DI RUMAH SAKIT UMUM YK MADIRA PALEMBANG - Rika Ariana; Fika Minata Wathan (Politeknik Kesehatan Kementerian Kesehatan Banten, 2020)
The one of Sustainable Development Goals (SDGs) in goals 3.2 are reducing Neonatal Mortality Rate to 12/1,000 live births. Preterm birth contributes greatly to neonatal morbidity and mortality. Based on the results of a review of the medical records of YK Madira Hospital in Palembang shows an increase the prevalence of preterm birth in 2018 of 5.7% and in 2019 an increase of 8.0%. The research aim to determine the relationship between risk factors on preterm birth. This research is an analytical survey, cross-sectional design using secondary with a systematic random sampling totaling 202 samples. Data analysis was performed using chi-square test for bivariate, logistic regression for multivariate, the results showed that there was a significant relationship between age (p-value = 0.000 OR = 3.4; 95% CI: 1.82-6, 39), education (p-value = 0.009 OR = 2.4; 95% CI: 1.28-4.58), history of preterm birth (p-value = 0.008 OR = 2.7; 95% CI: 1, 35-5.54), ANC examination (p-value = 0.031 OR = 2.5; 95% CI: 1.15-5.72) smoking variable obtain p-value = 1,000 (p>0.05). Conclusion: The most dominan variabel affecting preterm birth are age and history of preterm birth. These results can be used as a basis for information so that health workers can further improve communication, information,education on reproductive health in prospective brides and also groups of mother at high risk for premature birth as a promotive, preventive action thtat can prevent premature birth to support the achievement of government program targets in reducing the neonatal mortality rate in Indonesia.